Peran Teknologi Pendidikan di Era Millenial dalam Membangun Daya Saing Bangsa - Qurban Hajar; Sofyan Syamratulangi; Mujiono Sang Putra (Jurnal LENTERA: Jurnal Studi Pendidikan, 2022)
This study aims to determine the role of educational technology in the millennial era in building the nation's competitiveness. This study uses qualitative methods by collecting article data and direct research to describe the phenomena that occur in the field with the aim of obtaining data based on the types and sources of primary data obtained directly from direct sources to find an explanation of the secondary data. Data analysis techniques to determine the extent of the role of technology in learning. Based on the results of the study, it was found that the role of educational technology in the millennial generation, namely; 1) technology as a medium for obtaining information on the subject matter, 2) technology as a medium for exploring knowledge, 3) technology as an intermediary for teachers and students, 4) technology as a catalyst for the quality of education.